Pengaruh Model Pembelajaran Discovery Learning Terhadap Hasil Belajar (IPS) Siswa Kelas V di SD Negeri 05 Sungai Rotan - Astriani, Astriani; Idris, Muhamad; Suryani, Ida (Indonesian Research Journal on Education, 2023)
This study aims to determine the effect of the discovery learning model on learning outcomes (IPS) for fifth-grade students at SD Negeri 5 Sungai Rotan. The population in this study were participants in class V A and class V at SD Negeri 5 Sungai Rotan, with a total population of 44 people. The sample of this research is a simple random sampling technique. There is method used in this research is a quantitative method which type is quasi-experimental. Data analysis techniques used in descriptive statistics and inferential statistical analysis. Based on the results of data analysis using descriptive statistics for studentworksheets (LKS), the average value of 79.68 is in the medium category, the lowest score is 55, and the highest score is 93. And for social studies learning outcomes for fourth-grade students, it can be seen from the report card scores of students who meet the Minimum Completeness Criteria (KKM). The average value obtained is 79.43 in the medium category, the lowest score is 75 and the highest value is 86. The results of the inferential statistical analysis of the Effect of the Discovery Learning Model on Learning Outcomes (IPS ) show that the regression equation ^ = 68.330 + 0.139 X and obtained t.count = 4.291, t.table = 2.021 because t.count > t.table (4,291 > 2,021) so that Ha is accepted and Ho is rejected.Thus, it can be concluded that there is Influence of the Discovery Learning Model on Learning Outcomes (IPS) for Class V Students at SD Negeri 5 Sungai Rotan.